1993
DOI: 10.1111/j.1439-0434.1993.tb01321.x
|View full text |Cite
|
Sign up to set email alerts
|

A Histological Evaluation of Induced Resistance to Phytophthora infestans (Mont.) de Bary in Potato Leaves

Abstract: Systemically induced resistance against Phytophthora infestans in the potato cultivar 'Bintje' was studied histologically at the light microscopy level on the leaf surface, in the epidermis and in the mesophyll of challenged potato leaves. Systemic disease resistance was induced by a local pre-infection with the same fungus. On the leaf surface of induced plants, the germination of cysts was enhanced. In the epidermis of induced plants, papilla deposition increased and penetration decreased, whereas in the mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These cell wall modifications have been reported in the case of PGPR that protect plants against phytopathogens by activating ISR plant defense responses (Iavicoli et al, 2003; Desoignies et al, 2012; Weller et al, 2012; García-Gutiérrez et al, 2013). One of the consequences of ISR is thus the reinforcement of the cell wall through enhanced lignin synthesis and callose apposition (Kovats et al, 1991; Strömberg and Brishammar, 1993), which restricts the progression of phytopathogens through plant tissues (García-Gutiérrez et al, 2013). …”
Section: Impact Of Pgpr On Root System Architecture and Root Structurementioning
confidence: 99%
“…These cell wall modifications have been reported in the case of PGPR that protect plants against phytopathogens by activating ISR plant defense responses (Iavicoli et al, 2003; Desoignies et al, 2012; Weller et al, 2012; García-Gutiérrez et al, 2013). One of the consequences of ISR is thus the reinforcement of the cell wall through enhanced lignin synthesis and callose apposition (Kovats et al, 1991; Strömberg and Brishammar, 1993), which restricts the progression of phytopathogens through plant tissues (García-Gutiérrez et al, 2013). …”
Section: Impact Of Pgpr On Root System Architecture and Root Structurementioning
confidence: 99%
“…At the infection sites sugars are taken up by the attacking fungus, while the attacked plant tissues have high substrate requirements for the initiation of defense responses, e.g., the synthesis of pathogenesis-related (PR) proteins, phenylpropanoids, or papillum formation (Strömberg and Brishammar 1993;Morkunas et al 2005Morkunas and Gmerek 2007;Bolton 2009). It has been shown that the induction of defense is cost intensive (Swarbrick et al 2006).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…However, it seems to be not main point of defense reaction in this system, because the suppression was not dramatically enough to express the resistance. Contrast to that, callose formation, one of the defense reactions of plants against attack of pathogen (Strömberg and Brishammar, 1993; Kovats et al, 1991), was significantly increased at the penetration site on the leaves of M. luteus pre-inoculated plants at 1.0 × 10 7 cfu/ ml . Although it was not significantly increased in the plants pre-inoculated with P. putida , the callose was more formed (Fig.…”
Section: Discussionmentioning
confidence: 78%